If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + 5x = 9x + -14 Reorder the terms: 2(-3 + x) + 5x = 9x + -14 (-3 * 2 + x * 2) + 5x = 9x + -14 (-6 + 2x) + 5x = 9x + -14 Combine like terms: 2x + 5x = 7x -6 + 7x = 9x + -14 Reorder the terms: -6 + 7x = -14 + 9x Solving -6 + 7x = -14 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -6 + 7x + -9x = -14 + 9x + -9x Combine like terms: 7x + -9x = -2x -6 + -2x = -14 + 9x + -9x Combine like terms: 9x + -9x = 0 -6 + -2x = -14 + 0 -6 + -2x = -14 Add '6' to each side of the equation. -6 + 6 + -2x = -14 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = -14 + 6 -2x = -14 + 6 Combine like terms: -14 + 6 = -8 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4
| 4(x-3)-3=-27 | | 10+5y=50 | | x^2+4q-45=0 | | t^2+3t-6=0 | | 3(-2x+1)-2(x+13)=7x-4(1-x) | | 2(3m-1)=16 | | 5(b+2)=30 | | 2x+6x=-8+7x | | 4y+3=21 | | 9(-4)-(-2)= | | 9x+9=7-(5x-6) | | -4(6x-7)+8(9x+7)=2 | | 11x^2-7x-10=0 | | -3(w-9)+8w+1= | | -8(x-7)+2(2x+5)=10 | | (5x-3)=(14-48) | | 6(5+c)=5c-4 | | x(x-6)=391 | | 7x-1=4x-8(7+x) | | 0.16x+0.1y=0.08 | | 5x(12x-7)-4x(15x-11)=30+29x | | 30x=100+20x | | 3y+6x=36 | | 0.03x+0.09y=-0.27 | | 3(2f+4)=2(3-6) | | 3(5x+3)=36+6x | | -3x^2+7x+6=f(x) | | (x^3-27)(x^3-27)(x^3-27)=0 | | 5x(12x-7)-4x(15x-11)=30-29x | | -1/6(24)= | | 2/3(12)= | | 3c=2c+0 |